Optoelectronic properties comparison of 10 and 20 multi quantum wells Ga0.952In0.048N0.016As0.984/GaAs p-i-n photodetector for 1.0 µm wavelength - Megat Muhammad Ikhsan Megat Hasnan; M.S. Nordin; N. Nayan; K.A. Mohamad; N.F. Basri; A. Alias; Vicker, A.J.; I.M. Noor (Elsevier, 2022)
This study proves the addition of quantum wells to the intrinsic regions of p-i-n GaInNAs/GaAs has improved the performance of optoelectronic devices. The optoelectronic properties that contribute to the device's dark current and photocurrent need to be well understood to develop photo-response at longer wavelengths. This study reports an optoelectronic properties comparison of different quantum well number for Ga0.952In0.048N0.016As0.984/GaAs-based dilute nitride multi-quantum wells (MQWs) p-i-n photodetector devices. From photoluminescence (PL) analysis, 20 MQWs shows a higher PL peak than 10 MQWs. The maximum quantum efficiency (QE) is found to be 80.3% for 20 MQWs and 46% for 10 MQWs, where 20 MQWs being the highest QE value ever reported for GaInNAs-based MQWs photodetector. Current versus voltage (I–V) measurement shows that 20 MQWs produces lower dark current than 10 MQWs. Besides, 20 QWs sample produces a higher current density (−12.43 μAcm−2) than 10 MQWs (−7.52 μAcm−2) under illumination. Impedance spectroscopy analysis shows that a lower dark current of 20 MQWs is due to a high intrinsic resistivity and low dielectric loss peak compared to 10 MQWs. SimWindows simulation shows good correlation with responsivity analysis and impedance analysis where at −5 V, 20 MQWs produces higher responsivity (0.65AW-1) due to wider depletion region (deduce from conduction band profile) and lower intrinsic capacitance and dielectric loss (deduces from impedance analysis) than 10 MQWs (0.37AW-1). At room temperature, the detectivity (D*) of the 20 MQWs photodetector (7.12 × 1010 cmHz0.5W−1) is higher than 10 MQWS photodetector (4.89 × 1010 cmHz0.5W−1). Finally, the 20 MQWs's (4.02 × 10−11 WHz−0.5) has produces lower noise-equivalent power (NEP) than 10 MQWs (5.85 × 10−11 WHz−0.5). This study has successfully presenting an understanding of optoelectronic properties and simultaneously producing a sensitive photodetector with high quality, low-noise which is comparable with ∼1010 cmHz0.5W−1 of commercial III-V alloy based near-infrared GaAs-based photodetectors.